2015
DOI: 10.1371/journal.pone.0132838
|View full text |Cite
|
Sign up to set email alerts
|

Participation in Physical, Social, and Religious Activity and Risk of Depression in the Elderly: A Community-Based Three-Year Longitudinal Study in Korea

Abstract: BackgroundWe examined the longitudinal association between participation in individual or combinations of physical, social, and religious activity and risk of depression in the elderly.MethodsElderly subjects aged ≥60 years who completed the Living Profiles of Older People Survey in Korea (n = 6,647) were included. The baseline assessment, Wave 1, was conducted in 2008, and a follow-up assessment, Wave 2, was conducted in 2011. We defined participation in frequent physical activity as ≥3 times weekly (at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(96 citation statements)
references
References 47 publications
3
74
1
7
Order By: Relevance
“…Previous studies have shown that older adults’ social participation is associated beneficially with mental health [13, 14], as well as quality of life (QOL) [15], cognitive functioning [16], lower mortality [17] and morbidity [18]. Several studies have found that active engagement in volunteering, religious activities, and clubs are associated with better mental health and reduced levels of depressive symptoms [14, 1921]. Furthermore, it is reported that the impact of social participation on mental health differs by gender [2224]; one study, for example, indicates that frequent participation at church is related to low prevalence of depressive symptoms in older women, while the opposite relationship was found in older men [22].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that older adults’ social participation is associated beneficially with mental health [13, 14], as well as quality of life (QOL) [15], cognitive functioning [16], lower mortality [17] and morbidity [18]. Several studies have found that active engagement in volunteering, religious activities, and clubs are associated with better mental health and reduced levels of depressive symptoms [14, 1921]. Furthermore, it is reported that the impact of social participation on mental health differs by gender [2224]; one study, for example, indicates that frequent participation at church is related to low prevalence of depressive symptoms in older women, while the opposite relationship was found in older men [22].…”
Section: Introductionmentioning
confidence: 99%
“…Social activities are, by definition, carried out with others (interaction between the person and the social environment) . Previous studies suggest that participation in social activities, such as relationships with friends, or fellow inmates at the senior center, protects against depressive symptoms . Social activities affect mental health through various mechanisms, including stimulating bodily systems, helping a person to cope with difficulties, and reinforcing an individual's attachment to other psychosocial resources such as social support .…”
Section: Introductionmentioning
confidence: 99%
“…19 Previous studies suggest that participation in social activities, such as relationships with friends, or fellow inmates at the senior center, protects against depressive symptoms. 20,21 Social activities affect mental health through various mechanisms, including stimulating bodily systems, helping a person to cope with difficulties, and reinforcing an individual's attachment to other psychosocial resources such as social support. 22 On the other hand, a longitudinal study conducted across 10 European countries reported that participation in political or community organizations was associated with an increase in depressive symptoms 4 years later.…”
mentioning
confidence: 99%
“…The present study was carried out using data from the 2008 and 2011 Living Profiles of Older People Survey, which was initiated in 2008 as a nationwide 3‐year interval longitudinal survey in Korea. Details of the Living Profiles of Older People Survey design are described elsewhere . In brief, the survey used stratified two‐stage cluster sampling.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the Living Profiles of Older People Survey design are described elsewhere. 9 In brief, the survey used stratified two-stage cluster sampling. The primary sampling unit was based on the 2005 census frame, with secondary sampling units consisting of households with older residents.…”
Section: Study Sample (Data Source)mentioning
confidence: 99%